Shallow-water benthic hydroids from Tethys Bay (Terra Nova Bay, Ross Sea, Antarctica) - Álvaro L. Peña Cantero; BOERO, Ferdinando; PIRAINO, Stefano (Polar Biology, 2013)
The shallow-water hydrozoan Antarctic fauna is still poorly studied, and available knowledge mostly refers to samples gathered by traditional ship-operated gears. By scuba diving in the coastal areas off the Italian Antarctic station "Mario Zucchelli" (Ross Sea, Terra Nova Bay), in the austral summer 2002-2003, a total of 20 hydrozoan species were found, belonging to 10 families and 13 genera. As hypothesized, Anthoathecata (11 species), usually under-represented in collections from indirect sampling gears, are common as also are Leptothecata (9 species). Hydractiniidae and Hydractinia are the dominant family and genus, followed by Haleciidae and Halecium. A new species to science, Halecium exaggeratum sp. nov. is also described. Most species are either endemic to Antarctic waters or restricted to Antarctic/sub-Antarctic areas; only two species have a wider distribution. Material reared in aquaria at the Italian Antarctic Base Mario Zucchelli facilitated knowledge of the life cycle and reproductive biology of several species. In particular, Opercularella belgicae was found to liberate a medusa stage referable to Phialella, and the species is assigned here to that genus, as Phialella belgicae. Also, extraordinary is the complete absence or scant representation of the most typical Antarctic benthic hydroid genera (Antarctoscyphus, Oswaldella, Schizotricha, Staurotheca, and Symplectoscyphus), likely related to the shallow limits of sampling (down to 48 m).